Conviviality and Survival: Co-Producing Brazilian Prison Order - Darke, Sacha (Palgrave Studies in Prisons and Penology Ser., 2018)
Intro -- Acknowledgements -- Contents -- List of Figures -- 1 Self-Governing Prison Communities -- Managing in Prison -- Getting By -- Mutual Aid -- References -- 2 Law and Repression -- The Great Incarceration -- Overcrowding -- Violent Iberian Realities -- References -- 3 The Northern Massacres -- References -- 4 Surviving through the Convívio -- Staff Shortage -- Conviviality -- Co-governance -- References -- 5 Managing without Guards -- The Colaboradores -- The Representantes -- No Guards -- Prisoners in Charge? -- References -- 6 Prison Gangs -- The Red Command -- The First Command of the Capital -- References -- 7 Co-producing Prison Order -- References -- References.